Music sampling and purchase intention in a developing African economy: An evaluation of the impact of consumer attitude and perceived value - Olugbenga Michael Adewumi; Chukwuemeka Echebiri; Atle Hauge (Journal of Tourism, Heritage & Services Marketing)
Purpose: This study investigates whether purchase intention is impacted by music sampling in piracy-prone emerging African markets and identifies the role of premium streaming perceived value as a driver in this relationship.